Performance and metabolic demand of a new repeated-sprint ability test in basketball players: Does the number of changes of direction matter? - Zagatto, A. M.; Ardigò, L. P.; Barbieri, F. A.; Milioni, F.; Dello Lacono, A.; Camargo, B. H. F.; Padulo, J. (The Journal of Strength and Conditioning Research, 2017)
This study compared 2 repeated-sprint ability (RSA) tests in basketball players. Both tests included 10 × 30-m sprints, with the difference that the previously validated test (RSA2COD) featured 2 changes of direction (COD) per sprint, whereas the experimental test (RSA5COD) featured 5 CODs per sprint. Test performances and metabolic demands were specifically assessed in 20 basketball players. First, RSA5COD test-retest reliability was investigated. Then, RSA2COD, RSA5COD sprint times, peak speeds, oxygen uptake (VO2) and posttest blood lactate concentration [La-] were measured. The RSA5COD results showed to be reliable. RSA2COD performance resulted better than the RSA5COD version (p < 0.01), with shorter sprint times and higher peak speeds. Over sprints, the tests did not differ from each other in terms of VO2 (p > 0.05). Over whole bout, the RSA2COD was more demanding than the RSA5COD, considering overall metabolic power requirement (i.e., VO2-driven + [La-]-driven components). Given that RSA5COD (a) mimics real game-play as sprint distance and action change frequency/direction and (b) has the same metabolic expenditure per task completion as metabolic cost, RSA5COD is a valuable option for players and coaches for training basketball-specific agility and assessing bioenergetic demands.